The Impact of Colombian Educational Language Policies on Language Teachers, Native Communities, and the Colombian Population (2021)
ABSTRACT:This literature review attempted to analyze articles dealing with the impact of Colombian educational language policies on language teachers, native communities, and/or the Colombian population in general. Thus, three categories were identified: Perpetuation of imbalanced relationships of power, Unveiling underlying discourses promoted by bilingualism policies, and Opening doors for challenging the established. Research revealed nothing has changed from 2009 until 2021 regarding how these policies promoted in Colombia are in detriment of linguistic minorities since the colonial days, helping the promotion of discourses of segregation and the exertion of asymmetrical power relationships. However, some scholars believe there is still hope for Colombians to change their perspective and critically oppose ideologies that undermine our history as a people.